Chính sách khoa học và công nghệ và việc vận dụng trong xây dựng cơ sở dữ liệu khoa học và công nghệ của Malaysia - Nguyễn, Minh Hoàng (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
Briefs Scientific and Technological Policy and its application to creation of Malaysian S&T  Database; describes S&T  database system of Malaysian Scientific and Technological Information Centre (MASTIC); makes clear some its experiences able to be referred to in creating the international S&T Database in Vietnam